Harmonic Elimination Pulse Width Modulation Using Differential Evolution Technique For Three Phase Voltage Source Inverter - Kamisman, Norazelina (2018)
Differential Evolution (DE) has been gaining popularity among researchers as an effective yet simple evolutionary algorithm to solve the optimization problems. This thesis presents an efficient and reliable DE based solution applied to the Harmonics Elimination Pulse Width Modulation (HEPWM) switching technique for three phase voltage source inverters. The proposed DE algorithm is able to compute optimal switching angles in HEPWM so that the switching scheme is able to eliminate lower order harmonic components of the three-phase inverter output voltage. Performance of the DE algorithm is highly affected by the mutant vector which is generated through a specific mutation process. Explanation of DE algorithm execution is given, and the best approach of mutation strategy selection used in DE has been investigated. Computation of DE algorithm and simulation of voltage source inverter using the calculated switching angles are carried out by using Matlab/Simulink software package. The proposed DE algorithm is also applied to the in-house developed experiment set-up which consists of three-phase inverter, gate driver, DC supply, resistive load and dSPACE software (ControlDesk Next Generation version 4.2.1) and dSPACE DS1104 R&D controller board. It has been confirmed through simulation and experiment that the proposed DE is able to eliminate lower order harmonics components and reduce the total harmonic distortion of three phase inverter output voltage.